Contagious bovine pleuropneumonia (lungsickness) in Africa : historical overview : Onderstepoort and veterinary research in Africa - W. Amanfu (Onderstepoort Journal of Veterinary Research, 2009)
Contagious bovine pleuropneumonia (CBPP) or lung sickness, is an insidious pneumonic disease of cattle caused by Mycoplasma mycoides subspecies mycoides small colony variant (MmmSC) and it is one of the major diseases affecting cattle in Africa. With the imminent eradication of rinderpest from Africa (Somali ecosystem) CBPP has become the disease of prime concern in terms of epizootics that affect cattle on the continent. The control and/or eradication of the disease have suffered from unsustained control actions due to lack of operational funds to support such actions and deterioration in the quality of veterinary services in many countries affected by the disease. Stamping out procedures which were adopted by Botswana to control the disease (1995-1997) cannot be carried out by many countries currently affected by CBPP due to the high financial cost, the widespread nature of disease, animal welfare considerations and the potential loss of a valuable genetic resource base. The current scenario of CBPP disease epidemiology in sub-Saharan Africa requires that proactive measures are taken to safeguard countries in southern Africa which are currently free from CBPP from being contaminated by the disease thus affecting the beef industry and people's livelihoods ; and to progressively control the disease in endemic zones of Western and Central Africa.